Answer :
Answer:
(8 + 6i)(7 – 9i) = (7 – 9i)(8 + 6i)
Step-by-step explanation:
commutative property of multiplication
abc = acb
We can change the order in which the multiplication is done
(8 + 6i)(7 – 9i) = (7 – 9i)(8 + 6i)
The example of the commutative property of multiplication can be seen in option (B) (8+6i)(7-9i) = (7-9i)(8+6i).
Commutative Property of multiplication
The commutative property of multiplication states that changing the factor's order does not change the answer.
What properties are used in the given equations?
Let's consider the first equation,
(8+6i) = (6i+8)
Here commutative property of addition is used.
So, this option is incorrect.
The given second equation is,
(8+6i)(7-9i) = (7-9i)(8+6i)
In the above equation, the commutative property of multiplication is used.
So, this option is correct.
Hence, option (B) (8+6i)(7-9i) = (7-9i)(8+6i) is the correct answer.
Learn more about the properties of multiplication here - https://brainly.com/question/1407048
#SPJ2